DEVELOPMENT OF LEARNING MODEL SMASH VOLLEYBALL BASED MULTIPLE TRAINING IN FACULTY OF SPORT SCIENCES STATE UNIVERSITY OF MEDAN - Sofyan hanif; Indra Kasih (Program Pascasarjana Universitas Negeri Jakarta, 2015)
This research is to development learning model smash volleyball based multiple training in State University of Medan. This method was research and development/R & D proposed by Borg and Gall (2005). Based on trial results found, multiple based learning model increaset the skill of volley ball smash technique mastery at faculty of Sport Science of Medan Stated University. Multiple training based learning model is wearing 7 group, and 21 forms of learning. 21 models of learning based training deemed necessary multiple training applied in each learning smash volleyball. The results of this the new model of learning assessment indicators is more effective than the old one. The average effectiveness of the attitudes perfect/SS indicator is older models of learning is 78.33% and 86.67% of new models of learning. The average of effectiveness in SW indicator is older models of learning is 73.33% and 80.00% of new models of learning. The average effectiveness of the NT indicator on older models of learning is 71.67% and 85.00% of new models of learning. The average effectiveness of the indicators of S^ on the old model of learning is 70.00% and 78.33% of new models of learning. Learning outcomes (average of all indicators) that reach increased from 73.33% to 82.50%. It can be concluded that multiple training based learning model more effective than the old learning model.